Exploring ERP Distortions to Reduce the Encoding Time of 360 Videos - Storch, Iago; Zatt, Bruno; Agostini, Luciano; Palomino, Daniel (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2021)
The encoding of 360 videos presents many challenges. These spherical videos require a planar projection stage prior to encoding, and there are no studies on how projection interferes with the encoder decisions. Also, due to the increased resolution, encoding 360 videos is computationally costlier than conventional videos. In this work, we perform an extensive evaluation of how the texture distortions caused by the projection interfere with the encoder’s behavior and exploit these interferences to propose multiple fast algorithms to accelerate the encoding. Experimental results show that the proposed algorithms reduce encoding time significantly with minor coding efficiency penalties, while the evaluations expose novel insights into the encoder behavior. The reached results are published in important events and journals.